ALPHA-GLUCOSIDASE INHIBITORY ACTIVITIES OF KEDABU FRUIT (Sonneratia ovata BACKER) ETHANOL EXTRACT AND FRACTION - Rahma Dona; Haiyul Fadhl; Mustika Furi; Tyasakti Viryana (Jurnal Farmasi Sains dan Praktis, 2021)
One of the antidiabetic activity tests is carried out through inhibition testing of the ɑ-glucosidase enzyme. Sonneratia ovata Backer is a mangrove plant that has been used traditionally in medicine. The antidiabetic activity of the fruit samples of Kedabu (Sonneratia ovata Backer) was tested by measuring the inhibition of the ɑ-glucosidase enzyme in vitro. The test sample used ethanol extract (EE) and 3 fruit fractions of Kedabu. The calculation result of the IC50 value obtained at EE was 1.86 µg / mL, the calculation result of the IC50 value obtained in the n-hexane (FH) fraction of Kedabu fruit was 193.32 µg / mL, the calculation result of the IC50 value obtained in the ethyl acetate fraction (FE) of fruit Kedabu is 2.32 µg / mL and finally the calculation result of the IC50 value of water fraction (FA) is 2.29 µg / mL. The positive control in this study, Akarbose, obtained an IC50 result of 0.75 µg / mL. Based on the results obtained, the ethanol extract of Kedabu (Sonneratia ovata Backer) fruit is very active and has the potential as an inhibitor of the ɑ-glucosidase enzyme, followed by the water fraction and ethyl acetate fraction, while the potentially inactive sample is in the n-hexane fraction.